2017
DOI: 10.1044/2016_lshss-16-0007
|View full text |Cite
|
Sign up to set email alerts
|

Synthesizing Information From Language Samples and Standardized Tests in School-Age Bilingual Assessment

Abstract: Purpose: Although language samples and standardized tests are regularly used in assessment, few studies provide clinical guidance on how to synthesize information from these testing tools. This study extends previous work on the relations between tests and language samples to a new population-school-age bilingual speakers with primary language impairment-and considers the clinical implications for bilingual assessment. Method: Fifty-one bilingual children with primary language impairment completed narrative la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 29 publications
1
32
0
Order By: Relevance
“…Associations between norm-referenced tests and conversational measures will be strongest on expressive measures of syntax, followed by measures of paragraph comprehension, then measures of pragmatic language. Previous researchers have demonstrated that MLUS correlates with some measures of standardized testing when using a narrative task [22,23]. Therefore, we expect the relationship between MLUS and a measure of syntactic construction to be stronger than the relationship between MLUS and comprehension or pragmatics.…”
Section: Current Studymentioning
confidence: 79%
See 3 more Smart Citations
“…Associations between norm-referenced tests and conversational measures will be strongest on expressive measures of syntax, followed by measures of paragraph comprehension, then measures of pragmatic language. Previous researchers have demonstrated that MLUS correlates with some measures of standardized testing when using a narrative task [22,23]. Therefore, we expect the relationship between MLUS and a measure of syntactic construction to be stronger than the relationship between MLUS and comprehension or pragmatics.…”
Section: Current Studymentioning
confidence: 79%
“…We expect TNW to be more strongly related to measure of syntactic construction than comprehension or pragmatics. Because previous researchers have indicated that the relationship between TNW from narrative language samples and norm-referenced language measures is only significant for older children [22,23], it is possible that, because the children in this study are younger, there will not be a significant relationship between the two. Hypothesis 3.…”
Section: Current Studymentioning
confidence: 85%
See 2 more Smart Citations
“…Informal measures reduce the bias of standardised norm-referenced assessments that over-identify students from culturally diverse or low socioeconomic backgrounds [40, 41]. For example, there is a growing body of evidence supporting the use of oral narrative tasks to appraise student language abilities in both monolingual and bilingual students [42, 43]. The findings from these studies indicate student performance on oral narrative tasks was similar for both groups of students, suggesting bilingual students were not disadvantaged by this measure [42, 43].…”
Section: Assessment Of Oral Language Proficiencymentioning
confidence: 99%